The role of emotion and reflection in the development of student teachers’ self-efficacy when analyzing video lessons - Schlosser, Anne; Paetsch, Jennifer (Frontiers in Psychology, 2023)
Teachers' self-efficacy is an important indicator of student teachers’ preparedness for teaching. Interventions using video lessons are effective in increasing student teachers' self-efficacy. However, there is a lack of research on emotional and reflective processes in the context of video-based interventions. The present study examined emotions and reflection as well as their effects on changes in self-efficacy in a video-based intervention. A total of 159 student teachers participated in the study. The participants were randomly assigned to three groups: Two groups analyzed video lessons. Group one received open-ended observation tasks (ig1) and group two received structured observation tasks (ig2). Participants in the control group (cg) analyzed text-based case studies with open-ended observation tasks. The results show that self-efficacy increased with medium effect size (d=.68) in video group two (ig2), which analyzed videos using structured observation tasks but not in video group one (ig1), which analyzed open-ended observation tasks, and the control group. In addition, significant relations between positive arousal and reflection emerged. Finally, regression analyses showed that reflection was a significant predictor for changes in self-efficacy, whereas no significant effect of emotional arousal was detected. In conclusion, the findings of this study indicate that video-based interventions with structured observation tasks increased self-efficacy among student teachers. In addition, the findings provide novel evidence on the role of emotions and reflection in video-based interventions in teacher education.